1991
DOI: 10.1111/j.1095-8649.1991.tb05074.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea trout stocking on the population genetics of landlocked brown trout, Salmo trutta L., in the Conwy River system, North Wales, U.K.

Abstract: The effect of the introduction of fry of anadromous sea trout, Sulmo rrurta L., on the genetic integrity of landlocked brown trout populations was evaluated. Samples were taken from six brown trout populations from streams above impassable waterfalls in the Conwy river system (North Wales, U.K.) in 1989 and 1990. Three ofthese streams had no known stocking history and three had been stocked with sea trout fry from the lower Conwy system over the last few years. Representatives of these sea trout were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
9
1
1
Order By: Relevance
“…There are no populations left for which stocking in the past or immigration by released fish can be totally excluded. Our results indicate genetic introgression of hatchery brown trout into natural populations which also has been reported from France (Barbat-Leterrier et al, 1989), Ireland (Taggart & Ferguson, 1986) and Britain (Hauser et a!., 1991). The intensively stocked populations clearly exhibited elevated genetic variability within the populations which is in accordance with expectations based on the varied origin of the hatchery stocks.…”
Section: Discussionsupporting
confidence: 78%
“…There are no populations left for which stocking in the past or immigration by released fish can be totally excluded. Our results indicate genetic introgression of hatchery brown trout into natural populations which also has been reported from France (Barbat-Leterrier et al, 1989), Ireland (Taggart & Ferguson, 1986) and Britain (Hauser et a!., 1991). The intensively stocked populations clearly exhibited elevated genetic variability within the populations which is in accordance with expectations based on the varied origin of the hatchery stocks.…”
Section: Discussionsupporting
confidence: 78%
“…The 'Atlantic' subdivision is proposed to extend to unglaciated areas of the southern British Isles and Brittany based on the predominance of the CKA1*115 allele and the LDHC*1OO allele (the marker allele of the 'ancestral race') reported in unstocked populations in these areas (Krieg & Guyomard, 1985;Hauser et at., 1991). The 'Mediterranean' subdivision is proposed to extend eastward through the Black and Caspian Seas based on the predominance of CKA1*1OO and LDHC*1OO throughout this area (Krieg & Guyomard, 1985;Osinov, 1988;Barbat-Leterrier et a!., 1989;Karakousis & Triantaphyllidis, 1990).…”
Section: Ancestral Originsmentioning
confidence: 99%
“…In a new environment, the stocks follow their inherited migration pattern in migration distance and direction (Jonsson, 1982;Jonsson et al, 1994;Brannon, 1984;Hansen et al, 1993;Kallio-Nyberg et al, 2000). There are, however, cases where a resident stock has evolved from an anadromous one when the barriers in a stream have prevented the feeding migration (Hindar et al, 1991;Hauser et al, 1991). Skrochowska (1969) observed that a resident type may evolve from an anadromous type, and vice versa.…”
Section: Evolution From Resident Type Into Migratory or Vice Versamentioning
confidence: 96%